(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Bursaphelenchus hildegardae sp. n. isolated from coniferous wood is described. The new species belongs to the ‘eggersi’ group. It is characterized by a body length of 911 (795-1000) ìm and 1032 (855-1335) ìm of males and females, respectively; slim body (a = 46); stylet 13 and 14 ìm long in males and females, respectively; lateral field with three lines; long postuterine branch; female tail with a finely rounded, strongly ventrally-bent terminus (c’ = 4.6); spicules 26 (23-28) ìm long and having a distinctly dorsally-bent condylus, and a dorso-ventrally visible terminal bursa. The new species differs from other species of the ‘eggersi’ group mainly by spicule shape, particularly by the thin hook-like condylus. It can be differentiated from B. eggersi and B. tusciae morphologically, by means of ITS-RFLP patterns and ITS1/2 rDNA sequences. The sequences distinguish the new species significantly from other Bursaphelenchus species.